Endovascular repair of traumatic aortic injury in a 16 month old - Scott Deeney; Jennifer L. Bruny (Elsevier, 2015)
Traumatic injury to the thoracic aorta is rare in children. We present the youngest reported case of traumatic thoracic aortic injury, occurring in a 16 month old (10 kg) male. Management emphases include identification and stabilization of all injuries, blood pressure control, timely repair of the aortic injury, and long-term radiographic follow-up. We demonstrate that endovascular repair at this age is feasible, but considerations such as small vessel diameter and patient growth may limit broad application. Long-term outcomes research in this population is necessary.